Detoxification of Reactive Carbonyl Species by Glutathione Transferase Tau Isozymes - Mano, Jun’ichi; Kanameda, Sayaka; Kuramitsu, Rika; Matsuura, Nagisa; Yamauchi, Yasuo (Frontiers in Plant Science, 2019)
Oxidative stimuli to living cells results in the formation of lipid peroxides, from which various aldehydes and ketones (oxylipin carbonyls) are inevitably produced. Among the oxylipin carbonyls, those with an α,β-unsaturated bond are designated as reactive carbonyl species (RCS) because they have high electrophilicity and biological activity. Plants have arrays of dehydrogenases and reductases to metabolize a variety of RCS that occur in the cells, but these enzymes are not efficient to scavenge the most toxic RCS (i.e., acrolein) because they have only low affinity. Two glutathione transferase (GST) isozymes belonging to the plant-specific Tau class were recently observed to scavenge acrolein with KM values at a submillimolar level. This suggests that GST could also be involved in the defense system against RCS. We tested the activities of 23 Tau isozymes of Arabidopsis thaliana for five types of RCS, and the results revealed that 11 isozymes recognized either acrolein or 4-hydroxy-(E)-2-nonenal or both as a substrate(s). Such RCS-scavenging activities indicate the potential contribution of GST to RCS scavenging in plants, and they may account for the stress tolerance conferred by several Tau isozymes. RCS are therefore a strong candidate for endogenous substrates of plant GSTs.